Microbial tolerance engineering toward biochemical production: from lignocellulose to products - Ling, Hua (2016)
Microbial metabolic engineering has been extensively studied for valuable chemicals synthesis, generating numerous laboratory-scale successes, and has demonstrated its potential to serve as a platform that enables large-scale manufacturing of many chemicals that are currently derived via chemical synthesis. However, the commercialization potential of microbial chemical production frequently suffers from low productivity and yields, where one key limiting factor is the inherently low tolerance of host cells against toxic compounds that are present and/or generated during biological processing. Consequently, various microbial engineering strategies have been devised to endow producer microbes with tolerance phenotypes that would be required for economically viable production of the desired chemicals. In this review, we discuss key microbial engineering strategies, devised primarily based on rational and evolutionary methodologies, that have been effective in improving cellular tolerance against fermentation inhibitors, metabolic intermediates, and valuable end-products derived from lignocellulose bioprocessing.